STUDI DESKRIPTIF KUANTITATIF TENTANG HUBUNGAN ANTARA POLA ASUH OTORITER ORANG TUA DENGAN PERILAKU AGRESIF PADA SISWA DI SMA NEGERI 1 AMURANG BARAT DAN SMA KATOLIK AQUINO AMURANG BARAT - Sengkey, Stevi B; Tiwa, Tellma M (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to determine the relationship between parental authoritarian parenting with aggressive behavior in public and private high school students. The hypothesis in this study is that there is a positive relationship between authoritarian parenting and aggressive behavior among students in public and private high schools. To test the research hypothesis, researchers took data using the Buss and Perry aggressive behavior scale (1992) which was adapted by Puteri (2015), and the authoritarian parenting scale from Ribeiro (2009) which was adapted by Hertanti 2014). The scale was distributed to 137 public and private high school students in Amurang Barat. Correlation analysis shows the coefficient of aggressive behavior and father's authoritarian parenting is r = 0.253 with a significance of p = 0.000 (p < 0.05) and the coefficient of aggressive behavior and mother's authoritarian parenting is r = 0.259 with a significance of p = 0.000 (p < 0.05) so that the hypothesis is accepted